Perayaan Pesta Nelayan Sebagai Daya Tarik Wisata Dalam Mempromosikan Pariwisata di Palabuhanratu Sukabumi - Lesmana, Andhika Chandra; Astuti, Nadya Ajeng (Universitas Pendidikan Indonesia, 2018)
This research was conducted in Palabuhanratu Sukabumi Regency, the aim of the study is to know about the organization of cultural tourism of fishermen party,tourist attraction of fishermanâ€™s day activities, and the effectiveness of tourism promotion of fishermanâ€™s day.This research uses descriptive qualitative research method and key informan as much as four people consisting of Tourism Office of Sukabumi Regency, Culture Youth and Sports Office, Fishermanday Chair, and Fishery Port of Nusantara Palabuhanratu. The result of research shows that, the organization of cultural tourism fishing party is very attractive for touristand held once a year which is followed by traditional ceremonies, cultural performances, parade of queen of fishermen and stakeholders, there is also a seaborn that the offerings to the sea andÂ entourage of cultural performance and tourist.